KRIMINALITAS, HEGEMONI, DAN POLITIK: PREMANISME DI YOGYAKARTA PADA MASA ORDE BARU - Ibrahim, Julianto (Jurnal Kawistara, 2024)
Indonesian democracy, despite being praised as an example of democracy in Muslim majority country, has been marked with the important role of non-state actors in influencing the social, economic, and political conditions of a society that are outside the government structure. One of the actors who play an important role in influencing the condition of society is the presence ofthugs and their acts of thuggery. This pattern of politics can be traced back to the ear of New Order. This research attempts to reveal and describe the actions carried out by thugs and their impact on the lives of the people of Yogyakarta during the New Order era. The method usedis the oral history method by interviewing the actors of non-state politics in Yogyakarta, primarily prominent young paramilitary or thug groups including Joxzin, Qizruh, Pemuda Pancasila and their relations with major political parties at that time, Golkar, PDIP and PPP. Thisresearch reveals that during the New Order era, thugs in Yogyakarta collaborated and cooperated with political forces. Political power utilizes thugs as a force that can suppress political opponents with violence and as a means of gaining votes in elections. Meanwhile, thugsjoin political forces with the intention of seeking political protection for their criminal acts and as a means of pursuing a career for a better future. Golkar in Yogyakarta used the mass organization Pemuda Pancasila (PP) as an element that could be used to suppress and intimidatepolitical opponents. Meanwhile, PPP and PDI used their party’s laskars (paramilitary wing) in securing and dealing with the violence they faced. The main strength of the laskars in PPP and PDI actually came from the wild youth organizations, namely Joxzin and Qizruh. For the twogroups, known for their violent repertoires, this presents an alternative to express themselves and a place to find identity. When the New Order rule ended in 1988, Qizruh leaders joined PP which meant supporting Golkar, and several other leaders chose to support PDI. Meanwhile,Joxzin’s elders had many careers as the main force of the laskars in PPP.